1998
DOI: 10.1109/18.669417
|View full text |Cite
|
Sign up to set email alerts
|

On the maximum tolerable noise for reliable computation by formulas

Abstract: It is shown that if a formula is constructed from noisy 2-input NAND gates, with each gate failing independently with probability ", then reliable computation can or cannot take place according as " is less than or greater than " 0 = (3? p 7)=4 = 0:08856 : : : .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 5 publications
2
56
2
Order By: Relevance
“…A stronger result along these lines had already been proven by William Evans and Nicholas Pippenger [19], but their purely classical proof is significantly more complicated.…”
Section: Proof Of the Main Theoremmentioning
confidence: 83%
“…A stronger result along these lines had already been proven by William Evans and Nicholas Pippenger [19], but their purely classical proof is significantly more complicated.…”
Section: Proof Of the Main Theoremmentioning
confidence: 83%
“…Evans and Pippenger [6] made some progress in this direction, showing that if a formula is constructed from independent -noisy, two-input NAND gates, then reliable computation can or cannot take place depending on whether is less than or greater than (3 0 p 7)=4 = 0:08856 . .…”
Section: Discussionmentioning
confidence: 99%
“…The error bound for each NAND gate in c17 is ε = 0.1055, which is greater than the conventional error bound for NAND gate, which is 0.08856 [6], [7]. The error bound of the same NAND gate in voter circuit (contains 10 NAND gates, 16 NOT gates, 8 NOR gates, 15 OR gates and 10 AND gates) is ε = 0.0292, which is lesser than the conventional error bound.…”
Section: Circuit-specific Error Bounds For Fault-tolerant Computationmentioning
confidence: 94%
“…Later this work was extended for k-input gates [5] where k was chosen to be odd. For a specific even case, Evans and Pippenger [6] showed that the maximum tolerable noise level for 2-input NAND gate should be less than (3 − √ 7)/4 = 0.08856 · · ·. Later this result was reiterated by Gao et al for 2-input NAND gate, along with other results for k-input NAND gate and majority gate, using bifurcation analysis [7] that involves repeated iterations on a function relating to the specific computational component.…”
Section: A State-of-the-artmentioning
confidence: 99%